First lactation performance of sows in Maternity Ring housing is comparable to that in farrowing crates - Plush, Kate J.; Chidgey, Kirsty L.; Young, Nigel; D’Souza, Darryl N.; van Barneveld, Robert J. (Frontiers in Veterinary Science, 2026)
There is a trade-off between sow and piglet welfare in farrowing pens, whereby increased behavioural freedom of sows results in unacceptable levels of piglet mortality. Improvements in sow welfare have been demonstrated in such housing systems; however, the footprint is often at least 50% greater than a standard farrowing crate. This remains an impediment to the adoption of confinement-free farrowing. The Maternity Ring, a system with a similar footprint to a farrowing crate, was designed to avoid close confinement of sows. However, its performance, particularly with regard to piglet survival, has not yet been quantified but is an essential part of evaluating commercial viability and acceptability in terms of piglet welfare. This experiment’s aim was to determine whether piglet mortality differed between farrowing crates and Maternity Rings. First-parity sows were recruited over 12 months and randomly allocated to one of the two treatments: farrowing crate (FC; n = 184) and Maternity Ring (MR; n = 205). Litter size and piglet mortality (number, age, and cause of death), as well as piglet fostering movements and medical interventions for sows and litters, were recorded. There was no difference in total pigs born, pigs born alive, or the number of pigs weaned between the two treatments. There was a tendency for a 0.3-pig-per-litter increase in pre-foster mortality in MR sows (p = 0.065), but pigs born dead, post-foster deaths, liveborn mortality, and total deaths were similar to FC sows. Piglet removal for ill thrift was 0.3 pigs per litter lower in MR sows (p = 0.05), and the incidence of medications in litters was reduced from 62 to 50% (p < 0.05). Additionally, sows were medicated less frequently in MR (6%) than in FC (15%, p < 0.05). MR housing achieved comparable liveborn piglet mortality to FC in first-parity sows. Future studies should test whether this performance is repeatable as sows are managed across multiple parities.